Compensatory Justice Nomos XXXIII - Chapman, John W. (NYU Press, 1991)
This Major Reference series brings together a wide range of key international articles in law and legal theory. Many of these essays are not readily accessible, and their presentation in these volumes will provide a vital new resource for both research and teaching. Each volume is edited by leading international authorities who explain the significance and context of articles in an informative and complete introduction.